PREDICTIVE MAINTENANCE ON FEED WATER PUMP AT PANGKALAN SUSU ELECTRIC STEAM POWER PLANT (PLTU) - Govin Hasiando Marpaung; Siti Anisa; Solly Aryza (Sean Institute, 2022)
Maintenance is an activity to keep the machine/production equipment, and make repairs or replacements to increase production in the industrial world. There are several types of maintenance developed, namely Preventive maintenance, corrective maintenance, and predictive maintenance. Maintenance techniques on direct object measurement monitoring are more applied to the industrial world because it is done without stopping operation on a machine, this treatment technique is also called predictive treatment, and requires analysis to monitor engine conditions, such as the measurement of vibration signals. Each vibration signal generated has different damage. Misalignment is one type of damage caused by the frequent vibration of the shaft and clutch. The vibration signal generated by misalignment has its own characteristic seen in the vibration spectrum. In this undergraduate task will be analyzed angular misalignment vibration signal at feed water pump by taking data at horizontal drive point. The vibration signal at the feed water pump generates angular misalignment through the 3X rpm spectrum where the first rpm is larger than the next two rpm. From the measurement of vibration, it can be seen through the comparison of vibration value to trending with the prevailing standard showing high amplitudes on the horizontal motor drive of 2.65 mm/s based on ISO 10816- 3 standard.